Could IFN-γ levels in serial QuantiFERON predict tuberculosis development in young children? - Villar-Hernández, Raquel; Latorre, Irene; Altet, Neus; Domínguez, José (Journal of Laboratory and Precision Medicine, 2017)
Tuberculosis (TB) is an infectious disease of important global health concern. On 2016, TB caused 10.4 million new cases and 1.8 million deaths (1). Compared to adults, young children infected with Mycobacterium tuberculosis (M.TB) are at high risk of progression and have an increased risk of developing a severe TB outcome (2). TB screening recommendations in children and other risk groups are described in several international and national guidelines, as well as the recommended prophylaxis (3,4). However, in some cases, prophylaxis may turn out to be unnecessary and depending on the setting it may be impossible to access. In order to better characterize who would benefit from prophylaxis, there is a need to identify those at a higher risk of developing active TB.